Evaluation of the American Society of Anesthesiologists Physical Status Classification System in Risk Assessment for Plastic and Reconstructive Surgery Patients. (March 2014) - Miller, Travis J.; Jeong, Haneol S.; Davis, Kathryn; Matthew, Anoop; Lysikowski, Jerzy; Cho, Min-Jeong; Reed, Gary; Kenkel, Jeffrey M.
Background: The American Society of Anesthesiologists Physical Status (ASA-PS) classification is a ranking system that quantifies patient health before anesthesia and surgery. Some surgical disciplines apply the ASA-PS to gauge a patient's likelihood of developing postoperative complications. Objective: In this study, the authors analyze whether ASA-PS scores can successfully predict risk for postoperative complications in plastic and reconstructive operations. Methods: The authors retrospectively reviewed the charts of 1801 patient procedures and selected for inclusion 1794 complex plastic and reconstructive operations that took place at 1 of several academic medical institutions between January 2008 and January 2012. ASA-PS scores, patient comorbidities, and postoperative complications were analyzed. Percentile data were treated with tests for proportions. Nonpercentile data were analyzed through comparison of means ( t test). Low-risk (ASA 1-2) and high-risk (ASA 3+) groups were compared with simple odds ratios. Results: For the 1430 women and 364 men in the patient cohort (average age, 49.5 years), the overall complication rate was 27.7%. When patients with complications were compared to those without, body mass index, operation time, recent major surgery, diabetes, hypertension, renal disease, cancer, and oral contraceptive use were statistically significant. After high-risk (n = 398) and low-risk (n = 1396) groups were identified, infection, delayed wound healing, deep vein thrombosis, and overall complications had significantly increased incidence in the high risk group. Notably, deep vein thrombosis displayed the highest odds ratio (4.17) and a complication rate increase from 0.93% to 3.77%. Conclusions: ASA-PS scores can be used either as substitutes for or as adjuncts to questionnaire-based risk assessment methods in plastic surgery. In addition to deducing significant findings for deep vein thrombosis incidence, ASA-PS scores hold important predictive associations for multiple non–venous thromboembolism complications, providing a broader measurement for postoperative complication risks. Level of Evidence: 4